2004
DOI: 10.2134/jeq2004.4960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloride in Soil Solution on the Plant Availability of Biosolid‐Borne Cadmium

Abstract: Increasing chloride (Cl) concentration in soil solution has been shown to increase cadmium (Cd) concentration in soil solution and Cd uptake by plants, when grown in phosphate fertilizer- or biosolid-amended soils. However, previous experiments did not distinguish between the effect of Cl on biosolid-borne Cd compared with soil-borne Cd inherited from previous fertilizer history. A factorial pot experiment was conducted with biosolid application rates of 0, 20, 40, and 80 g biosolids kg(-1) and Cl concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…In particular, anions have been recognized to greatly reduce sorption and enhanced mobility of Cd and Pb in soils by complexation of Cl − with these metals (Usman et al, 2005;Ghallab and Usman, 2007). Salinity change the bioavailability of heavy metals such as Cd and Pb in soil, irrespective of soil pH (Weggler et al, 2004) and it is found to be one of the key features in translocating metals from roots to foliar parts of the plants (Fitzgerald et al, 2003;Manousaki et al, 2009). Moreover, Sari and Din (2012) reported that physiological mechanisms in addition to metals speciation control the Cd and Pb uptake by Avicennia alba roots and further translocation to the stems and leaves in saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, anions have been recognized to greatly reduce sorption and enhanced mobility of Cd and Pb in soils by complexation of Cl − with these metals (Usman et al, 2005;Ghallab and Usman, 2007). Salinity change the bioavailability of heavy metals such as Cd and Pb in soil, irrespective of soil pH (Weggler et al, 2004) and it is found to be one of the key features in translocating metals from roots to foliar parts of the plants (Fitzgerald et al, 2003;Manousaki et al, 2009). Moreover, Sari and Din (2012) reported that physiological mechanisms in addition to metals speciation control the Cd and Pb uptake by Avicennia alba roots and further translocation to the stems and leaves in saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the effect of inorganic anionic complex formation on the adsorption of Cd 2+ by soils. Weggler et al (2004) showed that increasing chloride (Cl) concentrations in soil solution increase the cadmium (Cd) concentration in the soil solution and Cd uptake by plants. This suggests that soil-borne Cd is desorbed by chloride ligands in soil solution.…”
Section: Complexationmentioning
confidence: 99%
“…In humus-rich soils, ca. 75 % of the element occurs in complexes with organic compounds (Weggler et al 2004). Bioavailable cadmium present in the environment can be easily absorbed by organisms.…”
Section: Resultsmentioning
confidence: 99%
“…However, the anthropogenic sources of potentially toxic trace elements in agricultural soils include mining, smelting, waste disposal, urban effluent, vehicle exhausts, sewage sludge, pesticides, fertilizers application and so on (Wei and Yang 2010). In an ecological aspect, contamination may have a significant negative impact on soil as habitat for numerous soil organisms and plants (Ayodele and Oluyomi 2011;Boshoff et al 2014;Dalenberg and Driel 1990;Heikens et al 2001;Holoubek et al 2009;Kelepertzis 2014;Martínez-López et al 2014;Notten et al 2005;Weggler et al 2004;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%